2019
DOI: 10.1002/mpr.1773
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and diagnostic classification of mixed features in patients with major depressive episodes: A multicenter study based on the DSM‐5

Abstract: Objectives The purpose of this study was to evaluate the prevalence of mixed features using the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM‐5) and to examine how patients with mixed states would be classified using the DSM‐5. Methods In total, 12 hospitals participated in this study, and data on the demographic characteristics and clinical diagnoses of patients treated between October 2013 and September 2016 were obtained. We reviewed the data for opposite‐polarity symptoms accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
1
11
0
1
Order By: Relevance
“…13 A detailed and longitudinal appraisal is required to clarify the diagnosis, which may be further confounded by personality, substance use, and/or anxiety comorbidity. [35][36][37][38] Clinicians may use the Montgomery Asberg Depression Rating Scale (MADRS) 39 and the Young Mania Rating Scale (YMRS) 40 to evaluate severity of depressive and manic symptoms, respectively, in patients with mixed presentations. The Clinically Useful Depression…”
Section: Assessment and Diagnosis Of Dsm-5 Mixed Featuresmentioning
confidence: 99%
“…13 A detailed and longitudinal appraisal is required to clarify the diagnosis, which may be further confounded by personality, substance use, and/or anxiety comorbidity. [35][36][37][38] Clinicians may use the Montgomery Asberg Depression Rating Scale (MADRS) 39 and the Young Mania Rating Scale (YMRS) 40 to evaluate severity of depressive and manic symptoms, respectively, in patients with mixed presentations. The Clinically Useful Depression…”
Section: Assessment and Diagnosis Of Dsm-5 Mixed Featuresmentioning
confidence: 99%
“…[22][23][24] Moreover, recent studies have reported that major depressive episode (MDE) mixed features are characterized by a low prevalence, the predominance of anxious distress, the prevalence of cluster B personality disorders, and pharmacological treatment with antipsychotics. [25][26][27] Thus, as shown in Figure 1, the specifier "with mixed features" may indicate quantitative but not qualitative overlapping symptoms from one pole to the opposite pole in the dichotomization of mood disorders into bipolar and depressive disorders.…”
Section: Dichotomizing Mood Disorders Into Bipolar Disorders and Deprmentioning
confidence: 98%
“…Therefore, the authors suggest that this treatment should be considered in depression with mixed features, which is particularly common in bipolar disorders (2.2 in MDD vs 14.3% in BD) and related to high suicidality. 26,27 Rapid Antisuicidal Effect of Ketamine Suicidality accounts for 15-20% of deaths in BD patients. [28][29][30] Risk of suicidal act in BD patients with mixed or psychotic symptoms is one of the highest of all psychiatric disorders.…”
Section: Multiple Administrationmentioning
confidence: 99%
“…Therefore, the authors suggest that this treatment should be considered in depression with mixed features, which is particularly common in bipolar disorders (2.2 in MDD vs 14.3% in BD) and related to high suicidality. 26 , 27 …”
Section: Ketamine In Bipolar Disorder – Clinical Datamentioning
confidence: 99%